LINGUISTIC INTERFERENCE AND ITS RELATION TO UZBEK-TAJIK LANGUAGE CONTACTS (Scientific journal of the Fergana State University, 2023)
This article provides the information on one of the main problems of sociolinguistics of interference and its manifestation in the Uzbek and Tajik languages.